2020
DOI: 10.1177/0891988720964250
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Problems Are Related to a Worse Quality of Life and a Greater Non-Motor Symptoms Burden in Parkinson’s Disease

Abstract: Introduction: The aim of the present study was to examine the frequency of self-reported sleep problems and their associated factors in a large cohort of PD patients. Methods: PD patients and controls, recruited from 35 centers of Spain from the COPPADIS cohort were included in this cross-sectional study. Sleep problems were assessed by the Spanish version of the Parkinson’s disease Sleep Scale version 1 (PDSS-1). An overall score below 82 or a score below 5 on at least 1 item was defined as sleep problems. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
2
8
0
Order By: Relevance
“…Another important factor is mood. Like in other studies, the mean score of BDI didn’t change over time 18 , 22 , suggesting that depression-type frequency does not appear to change over time in PD 45 . Cross-sectional studies have reported the clear contribution of depression or a worse mood to a poorer QoL in PD patients 3 , 12 , 13 .…”
Section: Discussionsupporting
confidence: 66%
“…Another important factor is mood. Like in other studies, the mean score of BDI didn’t change over time 18 , 22 , suggesting that depression-type frequency does not appear to change over time in PD 45 . Cross-sectional studies have reported the clear contribution of depression or a worse mood to a poorer QoL in PD patients 3 , 12 , 13 .…”
Section: Discussionsupporting
confidence: 66%
“…With regard to sleep problems, there is a progressive increase in the frequency of sleep disturbances in PD, with the number of subjects reporting multiple sleep disturbances increasing over time [ 48 ]. Recently, we observed in the baseline analysis of the COPPADIS cohort that NMS burden was associated with sleep problems after adjustment for age, gender, disease duration, LEDD, H&Y, UPDRS-III, UPDRS-IV, PD-CRS, BDI-II, NPI, VAS-Pain, VAFS, FOGQ, and total number of non-antiparkinsonian treatments [ 49 ]. Here, after a 2-year follow-up we observed that changes in sleep predict changes in the global NMS burden.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between sleep disorders and mood disorders has been widely confirmed in different populations beyond PD patients, 4–6 , 25 , 33 and these comorbidities have mutual influence. 9 In drug-naïve patients with PD, poor sleepers were more likely to experience anxiety and depression, and we found this phenomenon is more substantial in female patients, which was consistent with Mahale’s finding.…”
Section: Discussionmentioning
confidence: 95%
“…In levodopa-treated patients with PD, sleep disruption is related with greater NMS burden and poorer life quality. 4 More central PD-related pain, 5 higher levodopa intake, 2 longer disease duration, 6 poorer cognition, 7 and more fatigue 8 are associated with worse sleep quality. Sleep disturbances and mood disorders often appear as comorbidities.…”
Section: Introductionmentioning
confidence: 99%